Influence Of Materials,Air Gap And Winding Turns For A Tubular Linear Switched Reluctance Actuator (TLSRA) - Md Ghazaly, Mariam; Yeo, Chin Kiat; Chong , Shin Horng; Jamaludin, Irma Wani; Ranom, Rahifa (Penerbit Universiti, UTeM, 2018)
This paper presents the design and optimization of Tubular Linear Switched Reluctance Actuator (TLSRA).The study is carried out by means of Finite Element Method (FEM)by using ANSYS Maxwell software which capable of predicting the TLSRA thrust force.The study covered the variation of three parameters which are actuator materials,actuator air gap thickness and number of winding turns.In this design,the medium carbon steel (AISI 1045) is used for the actuator materials due to lower materials cost and higher thrust force generated compare to low carbon steel (AISI 1008 & AISI 1010) at current applied more than 1.8 A.In order to overcome the issue of TLSRA on low force density,the optimization of actuator air gap thickness and number of winding turns are important parameters that will influence the inductance and magnetic flux of TLSRA.The results show that the actuator produced larger thrust force with the air gap thickness of 0.5 mm and number of winding turns of 300 turns where it reaches 10.16 N when 3.6 A current is applied.